2016
DOI: 10.1080/13880209.2016.1190764
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemum morifolium extract improves hypertension-induced cardiac hypertrophy in rats by reduction of blood pressure and inhibition of myocardial hypoxia inducible factor-1alpha expression

Abstract: (2016) Chrysanthemum morifolium extract improves hypertension-induced cardiac hypertrophy in rats by reduction of blood pressure and inhibition of myocardial hypoxia inducible factor-1alpha expression, Pharmaceutical Biology, 54:12, 2895-2900, DOI: 10.1080/13880209.2016 Context: Chrysanthemum morifolium Ramat. (Asteraceae) extract (CME) possesses a vasodilator effect in vitro. However, the use of polyphenol-rich CME in the treatment of hypertension-induced cardiac hypertrophy has not been reported. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Hemsl. exhibited a vasodilatory effect by reducing the blood pressure of cardiac hypertrophy rats (Gao et al, 2016). The major phytochemicals in this extract are 4,5-di-caffeoylquinic acid, 3,5dicaffeoylquinic acid, luteolin-7-b-glucoside, 3-chlorogenic acid (11), and apigenin-7-O-glucoside.…”
Section: Vasorelaxant and Vasodilation Actionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hemsl. exhibited a vasodilatory effect by reducing the blood pressure of cardiac hypertrophy rats (Gao et al, 2016). The major phytochemicals in this extract are 4,5-di-caffeoylquinic acid, 3,5dicaffeoylquinic acid, luteolin-7-b-glucoside, 3-chlorogenic acid (11), and apigenin-7-O-glucoside.…”
Section: Vasorelaxant and Vasodilation Actionmentioning
confidence: 96%
“…Extract (Gao et al, 2016) Crassocephalum crepidioides (Benth.) S. Moore Extract (Goldansaz et al, 2018) Inula racemosa Hook F. India, Asian Pushkarmool Hypotensive, antihyperlipidemic and antioxidant…”
Section: Chrysanthemum Vasodilation Flowersmentioning
confidence: 99%
“…The flower of C. morifolium has long been used as traditional Chinese medicine and beverage ( Ye et al, 2007 ). Modern pharmacological studies have demonstrated that C. morifolium possesses extensive bioactivities and has functions of anti-inflammation ( Cheon et al, 2009 ; Lee et al, 2009 ; Luyen et al, 2015 ), antioxidation ( Lin et al, 2010 ; Yang, 2011 ), anticancer ( Yuan et al, 2009 ; Wang et al, 2010 ; Yang et al, 2011 ; Kim et al, 2013 ), cardiovascular protection ( Jiang et al, 2005 ), and hepatoprotective ( Rusu et al, 2005 ; Gao et al, 2016 ). Component analysis of C. morifolium showed that flavonoids are the main bioactive compounds, such as luteolin-7- O -glucoside, quercetin-7- O -galactoside, apigenin-7- O -glucoside, diosmetin-7- O -glucoside, and acacetin-7- O -galactoside ( Lin and Harnly, 2010 ; Sun et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main bioactive components in the flowers of CM are flavonoids and phenolic acids, which are composed of chlorogenic acid, acacetin, apigenin, and luteolin, along with its glucoside form [ 7 ]. Previous studies have shown that CM and its components possess various biological functions, including antioxidant [ 8 ], anti-inflammatory [ 9 ], anti-tumorigenic [ 10 ], and cardiovascular-protective functions [ 11 ]. Moreover, the CM flower extract has been shown to prevent hyperlipidemic fatty liver disease by increasing hepatic peroxisome proliferator-activated receptor (PPAR)-α expression in hyperlipidemic fatty liver disease caused by high-fat milk [ 12 ].…”
Section: Introductionmentioning
confidence: 99%